Core muscle activation during dynamic upper limb exercises in women - Tarnanen, Sami P; Siekkinen, Kirsti M; Häkkinen, Arja H; Mälkiä, Esko A; Kautiainen, Hannu J; Ylinen, Jari J (Journal of strength and conditioning research, 2012)
Although several everyday functions and sporting activities demand controlled use of the abdominal and back muscles while working with the upper limbs, the activity of core muscles during dynamic upper limb exercises in the standing position has not been studied extensively. The purpose of this cross-sectional study was to examine abdominal and back muscle activity during dynamic upper limb exercises while standing and to evaluate whether dynamic exercises are appropriate for strengthening muscles. The activation of the rectus abdominis, obliquus externus abdominis, longissimus, and multifidus muscles during dynamic bilateral or unilateral shoulder exercises with or without fixation of the pelvis was measured in 20 healthy women using surface electromyography. Trunk muscle activation during isometric maximum contraction was used as a comparative reference. With bilateral shoulder extension and unilateral shoulder horizontal adduction, abdominal muscle activity was >60% of activity during reference exercises. With unilateral shoulder horizontal abduction and shoulder extension exercises, back muscle activity was >60% of the activity level reference exercise. Muscle activation levels were 35-64% lower during shoulder horizontal adduction and abduction without fixation compared with exercises with fixation. The results indicate that upper limb exercises performed in the standing position are effective for activating core muscles. Bilateral and unilateral shoulder extension and unilateral shoulder horizontal abduction and adduction with the pelvis fixed elicited the greatest activity of the core muscles.